2007
DOI: 10.1080/10286020500531993
|View full text |Cite
|
Sign up to set email alerts
|

New salirepin derivatives from Symplocos racemosa

Abstract: The phytochemical investigation of the n-butanol soluble fraction of the bark of stem of Symplocos racemosa Roxb. yielded two new phenolic glycosides of salirepin series, symplocuronic acid (1) and sympocemoside (2), while salirepin (3) was isolated for the first time from this plant. The structures of the new compounds were identified by 1D and 2D NMR techniques along with other spectral evidences and by comparison with the published data of closely related compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The phytochemical investigations of S. racemosa have mainly focused on the stems and barks, because these parts have long been used for medicinal purposes so far. The Pakistan research group exclusively reported phenolic glycosides and their biological activities from the bark of S. racemosa including salirepin, symplocuronic acid, sympocemoside [4], benzoyl salireposide, salireposide, four triterpenes, which featured phosphodiesterase inhibitory activity [5], symcomoside A and B, tortoside C, which showed α-glucosidase inhibitory acitivity, 1-ethyl brachiose-3'-acetate, nonaeicosanol and three fatty acid derivatives featuring lipoxygenase inhibitory acitivity [6], locoracemoside A, B, C describing α-chymotrypsin inhibitory activity [7]. Although phenolic glycosides and their biological activities have been well-reported so far, further phytochemical investigation of other constituents from S. racemomsa is required.…”
Section: Introductionmentioning
confidence: 99%
“…The phytochemical investigations of S. racemosa have mainly focused on the stems and barks, because these parts have long been used for medicinal purposes so far. The Pakistan research group exclusively reported phenolic glycosides and their biological activities from the bark of S. racemosa including salirepin, symplocuronic acid, sympocemoside [4], benzoyl salireposide, salireposide, four triterpenes, which featured phosphodiesterase inhibitory activity [5], symcomoside A and B, tortoside C, which showed α-glucosidase inhibitory acitivity, 1-ethyl brachiose-3'-acetate, nonaeicosanol and three fatty acid derivatives featuring lipoxygenase inhibitory acitivity [6], locoracemoside A, B, C describing α-chymotrypsin inhibitory activity [7]. Although phenolic glycosides and their biological activities have been well-reported so far, further phytochemical investigation of other constituents from S. racemomsa is required.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, its IR spectrum showed specific absorptions at 3442 cm 21 , which could be ascribed to the hydroxyl group. The intense IR absorption band at 1724 cm 21 revealed the presence of ester functionality, while the broad CZO stretching band in the region of 1076 cm 21 suggested its glycosidic nature [15].…”
Section: Resultsmentioning
confidence: 99%
“…The study done by Ahmed et,al it was reported that the bark of this tree is employed in many Ayurvedic formulations for the therapy of numerous illnesses, particularly gynaecological disorders, and possesses astringent, styptic, cooling, anti-inflammatory, and antimicrobial effects.The bark of this tree has astringent, styptic, cooling, anti-inflammatory & anti-microbial properties & is used in various Ayurvedic formulations meant for the management of many disorders especially in gynaecological disorders (14,15).…”
Section: Discussionmentioning
confidence: 99%